The Extent Of Availability Of Organizational Excellence Dimensions In Service Organizations (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of the research is to determine the availability of the dimensions of organizational excellence, represented by: (leadership, human resources, customer satisfaction, employee satisfaction, service quality, quality of operations), in service organizations, by applying to Syriatel Company in Lattakia Governorate.The research was based on the descriptive and analytical approach, and the research community included Syriatel employees, whose number is approximately (132) workers, where the questionnaire was distributed as a search tool to them, and (126) complete and valid questionnaires were returned for statistical analysis, with a response rate of (95.45%).The results showed that the level of organizational excellence in the company under study is a high level, with a relative importance of (75.16%). All the sub-dimensions of organizational excellence have obtained a high and convergent relative importance, the highest of which was the dimension of customer satisfaction, and the lowest of the quality of operations.